2020
DOI: 10.3390/ijms21061905
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Targeting ER Stress, and the Functional Link to Mitochondria

Abstract: The endoplasmic reticulum (ER) is a dynamic organelle essential for intracellular homeostasis maintenance, controlling synthesis, the folding of secreted and membrane-bound proteins, and transport of Ca2+. During cellular stress, ER dysfunction leads to the activation of unfolded protein response (UPR) due to accumulated misfolded proteins in the ER. This condition is referred as ER stress. Mitochondria and ER form a site of close contact (the mitochondria-associated membrane, MAM) which is a major platform ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 61 publications
1
60
0
Order By: Relevance
“…ER and mitochondria are closely related to each other, and their main tasks are Ca++ homeostasis, autophagy, and apoptosis, in addition to the regulation of innate and adaptive immune responses during viral infections [119] , [123] , [124] , [125] . Studies have identified several SARS-CoV proteins with an ability to manipulate ER and mitochondria proteins, and thus enabling the virus to escape from host cell defense and continue to replicate [119] , [122] .…”
Section: Inhibition Of Endoplasmic Reticulum-mitochondrial Stress As mentioning
confidence: 99%
See 2 more Smart Citations
“…ER and mitochondria are closely related to each other, and their main tasks are Ca++ homeostasis, autophagy, and apoptosis, in addition to the regulation of innate and adaptive immune responses during viral infections [119] , [123] , [124] , [125] . Studies have identified several SARS-CoV proteins with an ability to manipulate ER and mitochondria proteins, and thus enabling the virus to escape from host cell defense and continue to replicate [119] , [122] .…”
Section: Inhibition Of Endoplasmic Reticulum-mitochondrial Stress As mentioning
confidence: 99%
“…Besides, reduced oxidative phosphorylation would lead to T cell exhaustion [118] . Furthermore, by affecting Ca++ homeostasis, ROS causes Ca++ to leakage from the ER into the mitochondria, which ultimately leads to the destruction of the inner mitochondrial membrane [120] , [123] , [126] . Based on the pathology evidence of COVID-19 patients, viral particles in ER and mitochondria were observed to be dilated and swollen, respectively [120] .…”
Section: Inhibition Of Endoplasmic Reticulum-mitochondrial Stress As mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been found that ER and oxidative stress lead to impairment of the so-called unfolded protein response (UPR), which is a compensatory mechanism that contributes to maintenance of the myocardial cell integrity. This involves complex molecular pathways, probably driven by eukaryotic translation initiation factor 2 alpha (eIF2α) phosphorylation and protein kinase RNA-like ER Kinase (PERK) and leading to a compensatory response to ER stress, although this needs to be better clarified [ 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. Furthermore, an increase in intracellular Glucose-Regulated Protein 78 (GRP78), considered to be a chaperone of ER stress and, most importantly, a regulator of UPR, has been shown to play a role in these mechanisms [ 132 , 133 , 134 , 135 , 136 ].…”
Section: Emerging Pathophysiological Mechanisms Involved In the Onmentioning
confidence: 99%
“…In particular, activated during stress conditions, protein kinase RNA-like ER kinase (PERK) is a mediator of eIF2α phosphorylation following folded protein exposure, thus preventing protein synthesis by selectively prompting Activating Transcription Factor 4 (ATF4) translation in the instantaneous response to ER stress [141,142]. Importantly, ER stress markers are involved in the PERK/eIF2α signalling pathway, which also promotes ER stress and contributes to organ injury induced through ER stress-mediated apoptosis [145,146,147]. Increased intracellular GRP78, considered to be a marker of unfolded protein response (UPR) and chaperone of ER stress, demonstrates unfolded and mis-folded protein aggregation in ER and UPR [148,149].…”
Section: Sarcoplasmic Reticulum Stress In Hfmentioning
confidence: 99%